Study on Orchid Diversity in Gunung Simpang Nature Reserve, West Java - DWI MURTI PUSPITANINGTYAS (Biodiversitas Journal of Biological Diversity, 2005)
Gunung Simpang Nature Reserve is located in West Java Province. It covers a 15.000 hectare area of highland forest, the altitude range between 800 to 1823 m asl. Orchid inventory and exploration were conducted to study orchid diversity in this conservation areas. Living plant was collected for ex situ conservation purpose in Botanic Garden. Observation on the population of terrestrial and epiphyte orchid was also done to study the dominant orchid in that area. It was recorded that there were 137 orchid species belonging to 51 genera, 95species of which were epiphytes and 42 other species were terrestrial orchids. 134 species of which were collected in Cibodas Botanic Garden, which is suitable place for highland plant. The most dominant terrestrial orchid was Plocoglottis javanica. Other species were also abundantly found, such as Phaius pauciflorus, Liparis rheedii, Diglyphosa latifolia, Neuwiedia zollingeri var. javanica, Calanthe ceciliae, C. speciosa and Phaius callosus. Some epiphyte orchids were very common found, that are Agrostophyllum majus, Coelogyne speciosa, Dendrobium mutabile, Agrostophyllum bicuspidatum, Pholidota ventricosa and Eria javanica. Some attractive orchids are potential for ornamental plant, such as Vanda tricolor, Phaius callosus, Phaius tankervilleae, Arundina graminifolia, Bulbophyllum lobbii, Coelogyne speciosa, Calanthe ceciliae, Calanthe triplicata and Calanthe speciosa.Â© 2005 Jurusan Biologi FMIPA UNS SurakartaKeywords: orchid, Gunung Simpang Nature Reserve, diversity.